Application of an elastoplastic model to predict behaviors of Concrete-Faced Rock-fill Dam under complex loading conditions - Wei, Kuangmin; Zhu, Sheng (Journal of Civil Engineering and Management, 2015)
In this research, a simplified rotational kinematic hardening model with the concept of sub-loading was used to predict behaviors of Concrete-Faced Rock-fill Dam under complex loading conditions. The model can overcome the shortcomings of classic elastoplastic model (i.e. soil behaviors under cyclic loading-unloading can be predicted). Elastoplastic formula of the model was presented in detail. Then this model was verified with test results of coarse grained soils, under both monotonic loading and cyclic loading-unloading conditions. This model was also applied to analyze deformation of Shuibuya rock-fill dam, computed results and in-situ measurements are compared. Results showed that computed results were consistent with in-situ measurements in both construction and operation period. Results also showed that permanent deformation that was caused by fluctuations of the reservoir level can also be predicted by this rotational kinematic hardening model.